IN THE MEMORY OF THE SCHOLAR-ORIENTALIST GASANKHAN MIRZAMAGOMEDOVICH MIRZAMAGOMEDOV - Alibekova, Patimat Magomedovna; Tikaev, Gusejn Gadziibragimovic (History, Archeology and Ethnography of the Caucasus, 2020)
The article is devoted to the scientific contribution of the scientist-orientalist Hasankhan Mirzamagomedovich Mirzamagomedov (1954-2020), who passed away in September 2020. G.M. Mirzamagomedov was a recognized expert in the history of Dagestan, its manuscript monuments, epigraphy, sphragistics and Muslim law. The scholar developed a concept for the study of Dagestan Arabic-language manuscripts. G.M. Mirzamagomedov carried out on the basis of a comprehensive study, analysis and comparison of the Dagestan written sources in Arabic. His works are devoted to the most complex issues of source study and archeography.
Keywords: G.M. Mirzamagomedov; scientist-orientalist; Dagestan Arabic Studies; epistolary sources; Koranic studies; codicology; toponymy; Muslim law.